Tyre Labelled Noise Values in the Context of Environmental Protection: Weaknesses of the Method and Benefits of Silent Tyres - HAŁUCHA, Maciej; BOHATKIEWICZ, Janusz; MIODUSZEWSKI, Piotr; BERGE, Truls (Archives of Acoustics, 2025)
The purpose of this work was to examine the impact of the inadequacies in the current procedure for car tyre labelling, specifically in the context of environmental noise, and to present the benefits of adopting more realistic procedure with the use of low-noise tyres. This was done using two approaches: an impact analysis and a cost-benefit analysis. The calculations were performed to show this impact on environmental noise. This was done using the common noise assessment methods in Europe (CNOSSOS-EU) model (recommended for strategic noise mapping of EU countries), which was validated using test results from sound exposure level measurements on both ISO test track and on real road sections. Using the noise calculation results, a cost-benefit analysis was performed, incorporating financial analyses of both the current and projected situation under different strategies to reduce tyre/road noise.